2016
DOI: 10.1037/sgd0000167
|View full text |Cite
|
Sign up to set email alerts
|

Affirmative practice with transgender and gender nonconforming youth: Expanding the model.

Abstract: Affirmative care with transgender and gender nonconforming (TGNC) children and adolescents is a new framework under which many mental health clinicians now practice. It rests on a premise that appreciates diverse gender expressions and identities within society, and encourages the highest potential for individuals to follow their own paths to positive emotional well-being. Scientific understanding of the phenomenology of gender development in children and adolescents is scarce, and the gaps in knowledge limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 37 publications
3
73
0
6
Order By: Relevance
“…Further, clinicians have observed that the anxiety and distress exhibited by many trans* children dissipates immediately after the children are allowed to freely express their gender identities (Ehrensaft, ; Hill, Menvielle, Sica, & Johnson, ). Thus, leading clinicians specializing in gender (e.g., Edwards‐Leeper, Leibowitz, & Sangganjanavanich, ; Hidalgo et al, ) advise parents to be supportive and to follow their children's lead, as developmentally appropriate, as children explore and express their “true gender selves” (Ehrensaft, , p. 341).…”
mentioning
confidence: 99%
“…Further, clinicians have observed that the anxiety and distress exhibited by many trans* children dissipates immediately after the children are allowed to freely express their gender identities (Ehrensaft, ; Hill, Menvielle, Sica, & Johnson, ). Thus, leading clinicians specializing in gender (e.g., Edwards‐Leeper, Leibowitz, & Sangganjanavanich, ; Hidalgo et al, ) advise parents to be supportive and to follow their children's lead, as developmentally appropriate, as children explore and express their “true gender selves” (Ehrensaft, , p. 341).…”
mentioning
confidence: 99%
“…Edwards-Leeper and Leibowitz expand on both the APA and WPATH sets of guidelines for affirmative therapy. 40 They especially go into depth regarding TGNC children and adolescents, stating that supporting them can look different from supporting adults. This is because they are still developing their sense of identity and have more pressing family/social concerns than adults do, since they are in constant contact with their family and peers at school and home.…”
Section: Resultsmentioning
confidence: 99%
“…Another hypothesis is that perhaps processes of identity development related to adoption for these children who present as TGNC also uniquely contribute to shaping their gender identity in ways that may be distinct from those for children who are not adopted (Miller, 2016;Schumer et al, 2017). Regardless, it is clear that, for children who are adopted and who are TGNC, support and affirmation are critical to their health and well-being (APA, 2015b; Edwards-Leeper, Leibowitz, & Sangganjanavanich, 2016;Farr & Grotevant, 2019).…”
Section: Conversations With Adoption Personnel: Locating the Rising Smentioning
confidence: 99%